Tuning Organelle Specificity and Photodynamic Therapy Efficiency by Molecular Function Design - Liu, Zhiyang; Zou, Hang; Zhao, Zheng; Zhang, Pengfei; Shan, Guo-Gang; Kwok, Ryan T. K; Lam, Jacky W. Y; Zheng, Lei; Tang, Ben Zhong (ACS nano, 2019)
Efficient organic photosensitizers (PSs) have attracted much attention because of their promising applications in photodynamic therapy (PDT). However, guidelines on their molecular design are rarely reported. In this work, a series of PSs are designed and synthesized based on a triphenylamine-azafluorenone core. Their structure–property-application relationships are systematically studied. Cationization is an effective strategy to enhance the PDT efficiency of PSs by targeting mitochondria. From the molecularly dispersed state to the aggregate state, the fluorescence and the reactive oxygen species generation efficiency of PSs with aggregation-induced emission (AIE) increase due to the restriction of the intramolecular motions and enhancement of intersystem crossing. Cationized mitochondrion-targeting PSs show higher PDT efficiency than that of nonionized ones targeting lipid droplets. The ability of AIE PSs to kill cancer cells can be further enhanced by combination of PDT with radiotherapy. Such results should trigger research enthusiasm for designing and synthesizing AIE PSs with better PDT efficiency and properties.